Modeling The Digitalization of SMEs Through the Utilization of Crowdfunding: Stakeholder and Community Based Perspectives - Zulfahmi, Zulfahmi; Ginting, Ginta (Journal of International Conference Proceedings, 2023)
Digitizing SMEs is a breakthrough strategy to accelerate the development of SMEs in an inclusive and massive manner. One interesting phenomenon is the transformation of technology-based financial services known as financial technology (Fintech). In recent years, Fintech has encouraged the emergence of various new services in the financial sector including Crowdfunding. Crowdfunding is the practice of raising funds or investing by utilizing sites or websites that are easily accessible to anyone, including business doers (SMEs) who need alternative sources of funds immediately. This Crowdfunding-based financial service will take various party such as: investors, business doers, intermediaries, the Financial Services Authority, and the wider community. The ability of SMEs to develop connections to stakeholders and become actively involved in the community will have an impact on their ability to use crowdfunding. This research proposes a strategy that focuses on the theory and idea of stakeholder management and community engagement to figure out how SMEs involved in crowdfunding. This modeling is expected to be used as a research basis to encourage digitalization of SMEs, especially in providing solutions in finding accessible sources of funding.